2021
DOI: 10.1038/s41467-021-25169-3
|View full text |Cite
|
Sign up to set email alerts
|

High COVID-19 transmission potential associated with re-opening universities can be mitigated with layered interventions

Abstract: Controlling COVID-19 transmission in universities poses challenges due to the complex social networks and potential for asymptomatic spread. We developed a stochastic transmission model based on realistic mixing patterns and evaluated alternative mitigation strategies. We predict, for plausible model parameters, that if asymptomatic cases are half as infectious as symptomatic cases, then 15% (98% Prediction Interval: 6–35%) of students could be infected during the first term without additional control measures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 37 publications
3
56
0
2
Order By: Relevance
“…Our work suggests that asymptomatic testing is a useful supporting measure and can help to further reduce case numbers, having the most impact at low to medium levels of vaccination uptake. This corroborates previous findings reporting that asymptomatic testing is more impactful at higher reproduction numbers [8][9][10] . Reliably estimating uptake of asymptomatic testing is challenging.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our work suggests that asymptomatic testing is a useful supporting measure and can help to further reduce case numbers, having the most impact at low to medium levels of vaccination uptake. This corroborates previous findings reporting that asymptomatic testing is more impactful at higher reproduction numbers [8][9][10] . Reliably estimating uptake of asymptomatic testing is challenging.…”
Section: Discussionsupporting
confidence: 92%
“…Testing of asymptomatic individuals leads to increased case detection and may be particularly important in the university student population where, due to the younger age structure, cases are more likely to be asymptomatic 6,7 . Previous modelling of asymptomatic testing in a university found that adherence to testing and isolation was important for reducing transmission 8 , particularly at high values of the reproduction number [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…In a complementary way, collateral effects are discussed, formulating a scenario of impacts generated by the reduction of student mobility during this pandemic. The objective of this research is to diagnose energy consumption patterns during the COVID-19 pandemic, as well as the environmental and economic effects that make it possible to determine possible routes for restructuring the university energy system, and to establish the basis for the construction of new scenarios on the management and efficient use of electricity during and after the pandemic, encouraging the construction of alternative proposals for self-sufficiency through sustainable electricity supply strategies, also promoting reflection regarding energy consumption linked to the new normal and distance education schemes that, in the coming years, will be abundantly reproducible in most universities [48]. It is also expected to encourage the establishment of realities of satisfaction of electrical energy needs economically and with low environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…In order for universities to plan a safe return to campus, several studies have analyzed the potential for mitigation strategies to control COVID-19 transmission in a university setting [4][5][6][7][8][9][10][11][12][13][14]. Most of these studies have focused on masks mandates, contact tracing, routine testing, and physical distancing.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have focused on masks mandates, contact tracing, routine testing, and physical distancing. Some utilized social mixing data from contact surveys [1,9,15,16], whereas others relied on simulations of daily behavioural contacts among students [17]. Only a few of these studies have considered scenarios that include a highly vaccinated university population [1,2,16,18,19].…”
Section: Introductionmentioning
confidence: 99%